Relationship Between Transformational Leadership, Talent Management and Job Satisfaction: A Test of Perceived Organizational Support as Meditating Role - Simanjuntak, Afriani Liliani; Nawangsari, Lenny Christina (Indonesian Journal of Business Analytics, 2024)
This paper is to examines the effect of TL and talent management on job satisfaction. It also purposes to determines the meditating role of POS in relationship between transformational leadership and talent management on job satisfaction at the Secretariat General of the Ministry of Energy and Mineral Resources, Indonesia. This explicit research uses quantitative approach with Structural Equation Modelling via Partial Least Squares (PLS-SEM) method to carried out the evaluation of the measurement model, the evaluation of the structural model and the evaluation of the goodness and fit model. Total of the responses are 135 government employees in 15 divisions. Primary data was obtained by distributing questionnaires through print out paper and online. The result based on p-value shows that TL has  negative insignificant effect on job satisfaction, TM has a positive and significant effect on job satisfaction, POS has a positive and significant effect on job satisfaction, TL has a positive and insignificant effect on job satisfaction meditated by POS, TM has a positive and significant effect on job satisfaction meditated by POS. The findings suggestion that talent management variables should be examining and continuing to improved job satisfaction.